Electrocoalescence of water-in-oil droplets with a continuous aqueous phase: implementation of controlled content release - Frey, Christoph; Göpfrich, Kerstin; Pashapour, Sadaf; Platzman, Ilia; Spatz, Joachim P. (ACS omega, 2020)
Droplet-based microfluidics have emerged as an important tool for diverse biomedical and biological applications including, but not limited to, drug screening, cellular analysis, and bottom-up synthetic biology. Each microfluidic water-in-oil droplet contains a well-defined biocontent that, following its manipulation/maturation, has to be released into a physiological environment toward possible end-user investigations. Despite the progress made in recent years, considerable challenges still loom at achieving a precise control over the content release with sufficient speed and sensitivity. Here, we present a quantitative study in which we compare the effectiveness and biocompatibility of chemical and physical microfluidic release methods. We show the advantages of electrocoalescence of water-in-oil droplets in terms of high-throughput release applications. Moreover, we apply programmable DNA nanotechnology to achieve a segregation of the biochemical content within the droplets for the controlled filtration of the encapsulated materials. We envision that the developed bifunctional microfluidic approach, capable of content segregation and selective release, will expand the microfluidic toolbox for cell biology, synthetic biology, and biomedical applications.